Pulling strings [videorecording (DVD)] - Channing, Stockard; Arnold, Tom, 1959-; Camil, Jaime; Chaparro, Omar, 1974-; Ramsey, Laura, 1982- (Pantelion, 2013)
After his daughter's visa request to visit her grandparents in America is rejected, a single father and his loyal best friend do everything it takes to win over the Embassy worker who turned her down.